Efficacy of a mobile technology-based intervention for increasing parents' safety knowledge and actions: a randomized controlled trial - Lara B. McKenzie; Kristin J. Roberts; Rebecca J. McAdams; Mahmoud Abdel-Rasoul; Orie Kristel; Alison Szymanski; Sarah A. Keim; Wendy C. Shields (BMC, 2021)
Abstract Background Leading causes of unintentional child injury such as poisoning and falls are preventable, and the majority occur in the home. Numerous home safety interventions have been developed and tested to increase safety behaviors; however, no smart phone-based applications (apps) have been developed and evaluated for this purpose. The objective of this study was to evaluate whether a mobile technology-based health behavior change intervention, the Make Safe Happen® app, was an effective tool to increase safety knowledge and safety actions/behaviors for the prevention of child unintentional injuries in and around the home. Methods Data were collected in pretest and posttest online surveys from an existing nationwide population-based survey panel. Intervention subjects were randomized to organically (participant-driven) use the Make Safe Happen® app for 1 week, which provided home safety information and the ability to purchase safety products, while control participants were assigned to download and use an app about a topic other than home safety. The primary outcomes of safety knowledge and home safety actions were assessed by using linear mixed model regressions with intention-to-treat analyses. Results A total of 5032 participants were randomized to either the intervention (n = 4182) or control (n = 850) group, with 2055 intervention participants downloading and entering their participant IDs into the Make Safe Happen® app. The online posttest survey was completed by 770 intervention and 283 control subjects. Mean knowledge parent safety score increased at a greater rate for intervention than control subjects (p < 0.0001), and at posttest was significantly higher for intervention than control subjects (p < 0.0001). The percentage of intervention subjects who reported doing all one-time and repeated safety actions significantly increased from pretest to posttest (p < 0.0001 and p = 0.0001, respectively), but there was no change among the control subjects (p = 0.1041 and p = 0.9755, respectively). At posttest, this percentage was larger for intervention than control subjects only for repeated safety actions (p = 0.0340). Conclusions The mobile application significantly improved safety knowledge and safety actions for participants using the Make Safe Happen® app, although loss to follow-up was a limitation. The results of this study indicate the usefulness of widespread distribution and use of the Make Safe Happen® app. Trial registration number NCT02751203 ; Registered April 26, 2016.